Solving problems of uncertain data using fuzzy B-spline - Abd. Fatah Wahab,; Jamaludin Md. Ali,; Ahmad Abd. Majid,; Abu Osman Md. Tap, (Universiti Kebangsaan Malaysia, 2010)
The construction of a geometric model in Computer Aided Geometrical Design (CAGD) with uncertain data points are difficult and challenging. In this paper, the construction of a fuzzy B-spline model as a mathematical representation for the curve of uncertain data using fuzzy control points and deffuzified control points is discussed. Cubic fuzzy B-spline or defuzzified B-spline curve for uncertainty data problems will be described using the cubic fuzzy B-spline approximation methods which are defined through fuzzy and defuzzification control points. For solving uncertain data, a method of fuzzification and defuzzification of component fuzzy (defuzzify) data point together with their model was introduced. For testing the effectiveness of the model, several examples of curve simulation of the given data are also discussed.